An exploration of autobiographical narrative through figurative ceramic sculpture installation series / Syed Zamzur Akasah Syed Ahmed Jalaluddin - Syed Ahmed Jalaluddin, Syed Zamzur Akasah (2015)
The dichotomy between creative processes, practices and life is one of the main themes in historical-artistic process reflection in over the centuries from east to west. Within the contemporary art, autobiographical work opens up the possibilities of a new kind of relation between people of different background and the creation of art as to share the life story. This research is an exploration of personal narrative driven from life experiences as observer raised by a single parent. The interpretation establishes in artwork making from the idea supporting by the historical evidence, and artists references background from local to international who producing artwork basis to autobiographical narrative, and also the suitability of material used and its related to the ideas. By that, figurative form is chosen as to convey the ideas and clay used in forming the work of ceramic as a main character in delivering the ideas. Investigation and understanding in the process of art making begins with the use of clay as raw material be explored within the scientific calculation, and as well the connection of ideas and artwork be presented within the help of domestic objects, wooden boxes and be finalized in installation series as a final body of artwork.